Indonesia's Trade Policy Strategy through the Rail Industry for the Train Market in Africa - Devita Prinanda; Haryo Prasodjo (Trunojoyo University of Madura, 2023)
The Indonesian Railway Industry (INKA) has increased its export production, especially to other developing countries such as Bangladesh, the Philippines, and others. Since 2018, Indonesia has explored the railway industry market in Africa. However, several challenges such as market competition with China and Europe, the distance between Indonesia and Africa, as well as the purchasing power of the African region with the majority of developing and less developed countries are important notes for Indonesia's strategy. This research will discuss the opportunities, challenges, and strategies of INKA in exporting trains in the African region. The analysis of this research uses international trade politics through the Pure Exchange Model of Trade and Strategic Trade Policy. The Pure Exchange Model of Trade is used to explain INKA's position in international trade to understand INKA's opportunities and challenges in Africa. Meanwhile, Strategic Trade Policy is used to describe Indonesia's strategy in advancing the Indonesian Railway Industry in Africa. The results of the study show that Indonesia provides support through a series of policies such as subsidies and diplomacy to obtain projects in Africa. In the process, INKA experienced challenges such as intense competition. However, many opportunities are presented by INKA in terms of the quality factor and the government's persuasive ability.